Soil Nitrate Concentration araound Kawah Sikidang, Dieng Plateau, Central Java - Moro, Hendro Kusumo Eko Prasetyo; Santoso, Santoso (Universitas Ahmad Dahlan, 2013)
The area around kawas sikidang have a specifict environmental condition.